Mutation on JmjC domain of UTX impaired its antitumor effects in pancreatic cancer via inhibiting G0S2 expression and activating the Toll-like signaling pathway - Xiao-hua Shen; Shu-ping Xiong; Sheng-peng Wang; Shan Lu; Yi-ye Wan; Hui-qing Zhang (Molecular Medicine)
Abstract Background Recently, the incidence of pancreatic cancer (PC) has gradually increased. Research has shown that UTX mutants are critical in tumors. However, the underlying mechanisms remain incompletely understood. This study aimed to explore how UTX mutation would affect its related function in PC. Method Exome sequencing was used to analyze PC samples. MTT, transwell, and colony formation assays were performed to determine the cellular functions of PC cells. qRT-PCR, Western Blot, TUNEL, immunohistochemistry, CHIP, bioinformatics, and xenograft experiments were used to investigate the mechanism of UTX mutants in PC in vitro and in vivo. Results We compared exome sequencing data from 12 PC samples and found a UTX missense mutation on the JmjC structure. Through cellular functions and xenograft experiments, wild-type UTX was found to significantly inhibit PC malignant progression in vitro and in vivo, while UTX mutation notably impaired this effect. Furthermore, G0S2 was identified as the key target gene for UTX, and wild-type UTX significantly increased its expression, while mutant one lost this function to a certain extent both in vitro and in vivo. More importantly, G0S2 overexpression not only inhibited tumor malignant phenotype and drug resistance for Gemcitabine in PC but also effectively reversed the roles of UTX mutant with Toll-like signaling pathway involved. In terms of mechanism, UTX mutation elevated the H3K27me3 modification level of the G0S2 promoter, which decreased its expression in PC cells. Conclusion In conclusion, UTX mutant weakened the antitumor effect of wild-type UTX in PC by inhibiting G0S2 expression and activating the Toll-like signaling pathway.